Filipino Nurses Competencies and Their Perspective on Asean Integration - Balawag, Mary Jane; Cayena, Maria Hazel; Dela Torre, Bai Katherine T.; Hermoso, Girlie; Uson, Judelyn T. (JPAIR Multidisciplinary Research, 2018)
The study intends to determine the level of competencies (knowledge, skills, & attitude) based on the Philippine Nursing core competency standards and nurse’s perspective on Asean integration to match with their competencies and determine their readiness towards the alliance. A descriptive quantitative design was used. The Survey questionnaire was conducted among nurses (112) working in the government hospital in Region XII such as Cotabato City, General Santos City, Kidapawan City, and Koronadal City. Focus group discussion and key informant interview were utilized. Findings revealed that nurses have the high knowledge, very competent, and moderately favorable attitude towards their role in client care, leadership and management, and research. Common themes emerged are, a. Clueless about Asean integration; b. Filipinos are globally competent. Nurses do not have an idea of the Asean integration. But they were not threatened because they considered themselves globally competent. Despite the information dissemination of the government regarding Asean Integration, this significant information did not reach the nurses working in the clinical area. Nurses have a different understanding of the Asean integration phenomenon because of the degree of exposure. However, competency wise, Filipino nurse believed they could keep up with the demands made by the integration.